Design of Sales Information System for Goods at Alpar Wholesale Store in Jambi City Based on Web - Sauti Abrani; Maria Rosario; Errissya Rasywir (Institut Bisnis dan Teknologi Pelita Indonesia, 2025)
Alpar Wholesale Store is a store that sells various kinds of products for household needs. In the data processing process using handwriting, so there are still many obstacles in data processing, such as the difficulty of: To record sales data, planning previously planned activities because the data search process is considered slow, data does not appear automatically so it must be written repeatedly, and data cannot be integrated with each other because there is no database. The purpose of this study is to analyze the current system, to overcome the problems faced at the Alpar Wholesale Store, by designing a Web-Based Sales Information System Design at the Alpar Wholesale Store in Jambi City. The Research Framework that will be carried out in solving the problems discussed is, identifying, searching for information based on theoretical foundations, collecting data using observation and interview methods, analyzing to find solutions to the problems faced by the Alpar Wholesale Store. The system development method uses a waterfall model, the implementation of this study uses the PHP Programming Language and DBMS MySQL, to produce data processing applications that are expected to facilitate data processing and report creation.